Vitamin D Deficiency as a Risk Factor for Diabetic Retinopathy: A Systematic Review and Meta-Analysis - Claudia Elena Petrea; Laura Andreea Ghenciu; Roxana Iacob; Emil Robert Stoicescu; Dorel Săndesc (Biomedicines)
Diabetic retinopathy (DR), a significant microvascular complication of diabetes mellitus (DM), remains a major cause of vision loss worldwide. Vitamin D, recognized for its role in bone health, has also been implicated in various non-skeletal conditions, including DR. This systematic review analyzed data from 20 studies involving 22,408 participants to explore the relationship between vitamin D levels and DR. Studies were included based on strict eligibility criteria, ensuring they could distinctly classify participants into DR and non-DR groups and provide quantitative measurements of vitamin D levels. Of these, nine studies were included in the meta-analysis. The pooled analysis revealed a significant association between lower vitamin D levels and increased odds of DR, with a combined odds ratio (OR) of 1.15 (95% CI: 1.10–1.20) under the fixed-effects model and 1.17 (95% CI: 1.08–1.27) under the random-effects model. Mean serum vitamin D levels were lower in individuals with DR (18.11 ± 5.35 ng/mL) compared to those without DR (19.71 ± 7.44 ng/mL), with a progressive decline observed across DR severity stages. Subgroup analyses showed significantly lower levels of vitamin D in proliferative DR compared to non-proliferative stages. Heterogeneity (I2 = 89%) was noted, most probably due to geographic differences, varying methodologies for vitamin D measurement, and DR classification approaches. Secondary analyses indicated that vitamin D deficiency prevalence ranged from 27% to 95% in DR populations, highlighting its potential role in disease progression. This review highlights the need for longitudinal studies to better understand the causal relationship. The findings also call attention to a critical gap in the literature regarding the therapeutic role of vitamin D supplementation in preventing and managing DR. Addressing vitamin D deficiency as a modifiable risk factor in DM care may offer new avenues for reducing the burden of DR.